Micro and small enterprises as drivers for job creation and decent work - Caroline Reeg (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The World Development Report 2013 on `Jobs' estimates that, in the coming years, hundreds of millions of new jobs need to be created to keep up with demographic changes and population growth in low and middle income countries (LMICs). This will even be necessary to keep unemployment and underemployment rates at their current levels – let alone to substantially improve the employment situation. Further, evidence suggests that the majority of current jobs in LMICs do not lift people out of poverty. Thus, in order to reduce poverty, we do not just need more jobs; what we need as well – and more importantly – are more productive and thus better paying jobs, along with decent working conditions. Across high-, middle- and low-income countries, micro and small enterprises (MSEs) constitute the largest share of private-sector enterprises and account for the bulk of employment, at least in LMICs. Even though a large share of these MSEs are informal, they are also accountable for most of the job creation in low- and middle-income countries. However, much of the employment in MSEs is low productivity, low income and low quality employment. As a result, substantial controversy remains over the underlying growth assumptions, the job creation potential and the net contribution of MSEs to national employment. Here, job creation within MSEs is defined as the creation of new employment in existing MSEs as well as the job contributions that arise from new MSEs, such as through start-ups and the self-employed. This report argues that not all jobs created by MSEs are productive and hence conducive to economic development and poverty reduction. It is shown that only if MSEs implement innovation activities and thereby improve their competitiveness and market share can they contribute to the creation of productive jobs. However, only a very small group of affluent micro- and small entrepreneurs have shown that they have the potential to drive job creation and improvements in job quality. It is argued that various factors play a role in driving the enterprise growth and employment: (i) human capital (education, training and work experience) and private wealth; (ii) sector/industry focus; (iii) R&D and market research; (iv) workforce training and incentives; and (v) supportive networks. As the majority of MSEs lack the access to these enabling growth factors (that is, human, social and financial capital) few manage to overcome growth constraints, expand in employment and improve working conditions. The policy consequence resulting from this observation should, however, neither be an approach targeted exclusively on `gazelles', that is, high-growth MSEs, nor a withdrawal of small enterprise promotion policies. The author argues that the uneven distribution of financial, human and social capital inhibits productivity and employment gains amongst disadvantaged MSEs and further enhances structural inequalities in society. In order to drive productivity growth, job creation and decent work amongst all MSEs, policymakers should not forget to undertake more fundamental policy reforms and interventions. While there is no single policy approach applicable to all LMICs, this report shows that a variety of policy measures exist that can assist MSEs in productivity-enhancing and labour-friendly investments.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Armut und Ungleichheit